Studi Kasus Penderita Diabetes Mellitus Tipe 2 Ditinjau dari Protection Motivation Theory - Ariestya Magdalena Njotomulio; Andrian Pramadi (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
A healthy lifestyle, including health behavior, illness behavior, as well as sick role behaviorplay a key role in managing type 2 diabetes mellitus (T2DM) as well as limiting its complications. This qualitative descriptive with case study research design utilized a type 2 diabetes mellitus patient who had good Self-Management Diabetes aims to describe the formation of health behavior in patients with type 2 diabetes mellitus reviewed by using Protection Motivation Theory (PMT). PMT consists of five components, namely the Severity, Vulnerability, Response Effectiveness, Self Efficacy, and Fear. Results suggest that the five components in PMT can be used to predict behavioral intentions that are highly related to one’s behavior, and the information either from the environment or intrapersonal plays a role in giving results in the formation of behavioral intentions to make changes in lifestyle, which leads to the emergence of health behaviors.